2018
DOI: 10.24200/sci.2018.21093
|View full text |Cite
|
Sign up to set email alerts
|

Application of AG method and its improvement to nonlinear damped oscillators

Abstract: In this paper, a new and innovative semi-analytical technique, namely Akbari-Ganji's Method (AGM), is employed for solving three nonlinear damped oscillatory systems. Applying this method to nonlinear problems is very simple because, in the solving process of only a trial solution, the main di erential equation and its derivatives are required. The analytical solutions obtained by AGM are utilized to study the impact of amplitude on nonlinear frequency and damping ratio. It is found that AGM produces acceptabl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 31 publications
0
3
0
Order By: Relevance
“…10 −2 M silver nitrate was added to the supernatant to finally obtain a 10 −3 M solution. The synthesis occurred under a halogen-tungsten lamp and provided the opportunity to obtain 5-60 nm NPs [59].…”
Section: Fusarium Oxysporum Nps Synthesismentioning
confidence: 99%
“…10 −2 M silver nitrate was added to the supernatant to finally obtain a 10 −3 M solution. The synthesis occurred under a halogen-tungsten lamp and provided the opportunity to obtain 5-60 nm NPs [59].…”
Section: Fusarium Oxysporum Nps Synthesismentioning
confidence: 99%
“…Their study offers an efficient approach to rapidly establish the amplitude-frequency correlation of a nonlinear oscillator. The investigation conducted by Mohammadian and colleagues 24 focused on examining the applicability of the AGM and its enhancement for nonlinear damped oscillators. In 2021, El-Dib 25 utilized the HPM technique in conjunction with a rank-upgrading approach to achieve superior results in nonlinear oscillation.…”
Section: Introductionmentioning
confidence: 99%
“…Since proposed by Benzi et al (1981) as an explanation of the observed periodicity in the ice ages on earth, stochastic resonance (SR) has officially entered scholar’s vision. Compared with traditional methods (Blanco-Velasco et al, 2008; Fan and Zheng, 2007; Grafov and Grafova, 2000; Mohammadian and Shariati, 2018), which were limited to expensive equipment and low signal-to-noise ratio (SNR), SR has become a research hotspot for its great advantages.…”
Section: Introductionmentioning
confidence: 99%